IMPACTS OF HIV ON PREGNANCY: A LITERATURE REVIEW - Barbosa, Rafael Soares; Silva , Roberta Lima; Moraes , Lael Mendonça; Dias , Luiz Paulo Leite Barros da Cunha; de Siqueira , Vincícius Alves Borges; Mendes, João Pedro de Carvalho Pereira; Fialho, Guilherme Matteucci Bezerra; Neto , Antônio Coelho e Silva; Freitas , Dara Farias; Faustino , Victor Botelho de Araújo; Neto , José Nilo Ribeiro; Matos, Thiago Henrique Ferreira; et al. (Seven Editora, 2024)
The Human Immunodeficiency Virus (HIV) is a pathogenic agent associated with consequences that involve, above all, the impairment of the immune system of the affected patient, resulting in vulnerability to opportunistic infections. The methodology used in this study was a qualitative review of the literature, where ten articles found in the Pubmed, SciELO and Google Scholar databases of the last five years were selected, aiming to understand the impacts of HIV on pregnancy. In the results found, it was possible to observe that HIV in the gestational period has the impacts of increasing the possibility of developing congenital malformations, intrauterine growth restriction, low birth weight and birth in small size for gestational age; in addition to the chance of dysregulation of the maternal-fetal binomial, when associated with the use of illicit drugs. It is therefore concluded that there is a need for constant surveillance and preparation of the health system for the management of HIV cases during the completion of pregnancy, in view of the possible negative complications associated with this condition. DOI:https://doi.org/10.56238/sevened2024.037-010